Gwasrapidd: an R package to query, download and wrangle GWAS catalog data - Magno, Ramiro (2020)
The National Human Genome Research Institute Catalog of Published Genome-Wide Association Studies (GWAS) Catalog has collected, curated and made available data from over 7100 studies. The recently developed GWAS Catalog representational state transfer (REST) application programming interface (API) is the only method allowing programmatic access to this resource.